A comparative study of endoscopic and conventional septoplasty - Soma Mandal; Sonali Jana (International Journal of Medical Research and Review, 2020)
Objective: Nasal obstruction due to deviated nasal septum is a common problem encountered by otolaryngologist. The standard surgical treatment for symptomatic deviated septum is septoplasty which has gone through several modifications since its inception. Study objectives were to compare the endoscopic and conventional septoplasty and to evaluate the advantage, disadvantage and complication of both the procedures.Materials and Methods: Prospective observational study was conducted in department of ENT and Head-Neck-Surgery of a tertiary care teaching hospital. Sixty patients undergoing either endoscopic septoplasty or conventional septoplasty were studied prospectively for a period of 3 months to compare the efficacy of both the techniques. Objective assessment was done by doing nasal endoscopy 90 days after the operation to note the following points- (1) Persistence of deviation (2) Spur (3) Formation of synechiae (4) Septal perforation.Result: In this study the endoscopic approach showed better overall clinical result as compared to conventional technique with lesser complication. It was noted that endoscopic septoplasty group had minimum blood loss and shorter operative time than conventional method, but difference was not statistically significant.Conclusion: Endoscopic septoplasty was founded with distinct advantage over conventional method due to better illumination, improve accessibility to remote area was founded. Further surgical experience and larger similar studies will help in coming to a greater consensus.